The witches - Dahl, Roald (b, 1985)
A young boy and his Norwegian grandmother, who is an expert on witches, together foil a witches' plot to destroy the world's children by turning them into mice.
Keywords: Witches -- Juvenile fiction; Grandmothers -- Juvenile fiction; Witches -- Fiction